Experimental and Clinical Studies on the Effects of Natural Products on Noxious Agents-Induced Lung Disorders, a Review - Saadat, Saeideh; Beigoli, Sima; Khazdair, Mohammad Reza; Amin, Fatemeh; Boskabady, Mohammad Hossein (Frontiers in Nutrition, 2022)
The harmful effects of various noxious agents (NA) are well-known and there are reports regarding the induction of various lung disorders due to exposure to these agents both in animal and human studies. In addition, various studies have shown the effects of natural products (NP) on NA-induced lung disorders. The effects of various NP, including medicinal plants and their derivatives, on lung injury induced by NA, were reviewed in this study. The improving effects of various NP including medicinal plants, such as Aloe vera, Anemarrhena asphodeloides, Avena sativa, Crocus sativus, Curcuma longa, Dioscorea batatas, Glycyrrhiza glabra, Gentiana veitchiorum, Gentiopicroside, Houttuynia cordata, Hibiscus sabdariffa, Hochu-ekki-to, Hippophae rhamnoides, Juglans regia, Melanocarpa fruit juice, Mikania glomerata, Mikania laevigata, Moringa oleifera, Myrtus communis L., Lamiaceae, Myrtle, Mosla scabra leaves, Nectandra leucantha, Nigella sativa, Origanum vulgare L, Pulicaria petiolaris, Paulownia tomentosa, Pomegranate seed oil, Raphanus sativus L. var niger, Rosa canina, Schizonepeta tenuifolia, Thymus vulgaris, Taraxacum mongolicum, Tribulus Terrestris, Telfairia occidentalis, Taraxacum officinale, TADIOS, Xuebijing, Viola yedoensis, Zataria multiflora, Zingiber officinale, Yin-Chiao-San, and their derivatives, on lung injury induced by NA were shown by their effects on lung inflammatory cells and mediators, oxidative stress markers, immune responses, and pathological changes in the experimental studies. Some clinical studies also showed the therapeutic effects of NP on respiratory symptoms, pulmonary function tests (PFT), and inflammatory markers. Therefore, the results of this study showed the possible therapeutic effects of various NP on NA-induced lung disorders by the amelioration of various features of lung injury. However, further clinical studies are needed to support the therapeutic effects of NP on NA-induced lung disorders for clinical practice purposes.